Multiple Mechanosensory Modalities Influence Development of Auditory Function - Horowitz, Seth S. (Society for Neuroscience, 2007)
Sensory development can be dependent on input from multiple modalities. During metamorphic development, ranid frogs exhibit rapid reorganization of pathways mediating auditory, vestibular, and lateral line modalities as the animal transforms from an aquatic to an amphibious form. Here we show that neural sensitivity to the underwater particle motion component of sound follows a different developmental trajectory than that of the pressure component. Throughout larval stages, cells in the medial vestibular nucleus show best frequencies to particle motion in the range from 15 to 65 Hz, with displacement thresholds of <10 μm. During metamorphic climax, best frequencies significantly increase, and sensitivity to lower-frequency (<25 Hz) stimuli tends to decline. These findings suggest that continued sensitivity to particle motion may compensate for the considerable loss of sensitivity to pressure waves observed during the developmental deaf period. Transport of a lipophilic dye from peripheral end organs to the dorsal medulla shows that fibers from the saccule in the inner ear and from the anterior lateral line both terminate in the medial vestibular nucleus. Saccular projections remain stable across larval development, whereas lateral line projections degenerate during metamorphic climax. Sensitivity to particle motion may be based on multimodal input early in development and on saccular input alone during the transition to amphibious life.